Protocol Adherence in Prehospital Medical Care Provided for Patients with Chest Pain and Loss of Consciousness; a Brief Report - Mehrara, Mostafa; Tavakoli, Nader; Fathi, Marzieh; Mahshidfar, Babak; Zare, Mohammad Amin; Asadi, Azita; Hosseinzadeh, Saeedeh; Safdarian, Mehdi (Archives of Academic Emergency Medicine, 2016)
Introduction: Although many protocols are available in the field of the prehospital medical care (PMC), there is still a notable gap between protocol based directions and applied clinical practice. This study measures the rate of protocol adherence in PMC provided for patients with chest pain and loss of consciousness (LOC). Method: In this cross-sectional study, 10 educated research assistants audited the situation of provided PMC for non-traumatic chest pain and LOC patients, presenting to the emergency department of a tertiary level teaching hospital, compare to national recommendations in these regards. Results: 101 cases with the mean age of 56.7 Â± 12.3 years (30-78) were audited (55.4% male). 61 (60.3%) patients had chest pain and 40 (39.7%) cases had LOC. Protocol adherence rates for cardiac monitoring (62.3%), O2 therapy (32.8%), nitroglycerin administration (60.7%), and aspirin administration (52.5%) in prehospital care of patients with chest pain were fair to poor. Protocol adherence rates for correct patient positioning (25%), O2 therapy (75%), cardiac monitoring (25%), pupils examination (25%), bedside glucometery (50%), and assessing for naloxone administration (55%) in prehospital care of patients with LOC were fair to poor. Conclusion: There were more than 20% protocol violation regarding prehospital care of chest pain patients regarding cardiac monitoring, O2 therapy, and nitroglycerin and aspirin administration. There were same situation regarding O2 therapy, positioning, cardiac monitoring, pupils examination, bedside glucometery, and assessing for naloxone administration of LOC patients in prehospital setting.